A competência da justiça do trabalho, a incapacidade laborativa do trabalhador e os benefícios previdenciários: (na perspectiva da dignidade da pessoa humana e do mínimo existencial) - Treviso, Marco Aurélio Marsiglia (2012)
In everyday life forensics, is increasingly common situation of employees and employers do not know the path that should take when one worker, who was for a period away from work activities realizing their social security benefits, receive a medical discharge from the National Institute Social Security (INSS), attends the company\'s headquarters and this, however, does not authorize the return to work, because it still considers him unfit for regular professional development activities for which he was hired. Worker is removed from their source of income. Receives no salary and other benefits. She receives social security benefits. You can not harness their labor services to another borrower. The result is harmful: it can not provide the necessary means for the acquisition of tangible and intangible assets necessary to live with dignity. The social value of work and the dignity of the citizen worker are not respected. The worker knocks on the doors of the judiciary, requiring the adoption of a decision that will restore dignity. We must therefore seek a solution which is legally feasible to check the judicial persecution. It is necessary that this decision will safeguard the security of the existential minimum. The concepts of state and its evolution, the legal system as a system of values and systematic interpretation of constitutional provisions, seeking to enforce the principle of human dignity, will assist us in this way. Are such lessons, the foundation for the work they intend to develop for in the end give the Labour Court an extremely important role in the recovery of the dignity of the worker.